State of care in patients with cervical cancer in Zaporozhzhia region since 2008 to 2015 year - O. P. Kolesnik; A. V. Kadzhoian; A. O. Kabakov (Zaporozhye State Medical University, 2016)
Cervical cancer remains an important problem of modern oncology. The aim of our study was to analyze morbidity and survival of patients with cervical cancer in the Zaporizhzhia region since 2008 to 2015 years and to investigate the state of care in this patient's category. Materials and methods. In the course of study it has been found that from 2008 to 2015 years in the Zaporizhzhia region 1312 cases of cervical cancer had been diagnosed. Moreover, the overall 5-year survival rate of patients was 58.7%. The highest 5-year survival has been observed in patients aged from 45 to 60 years (62.1%). During the analysis of patients' survival (taking the stage of cervical cancer into account) it has been noted that the overall 5-year survival in the 1-st stage of the disease was 85.4%, while the 2-nd stage - 52.8%, 3-rd stage - 26.9% and at stage 4 - 8.3%. Overall 5-year survival in patients with adenocarcinoma of the cervix was 48.8%, and in patients with squamous cell cancer - 60.5%. We have analyzed the survival rate after treatment. The first place in terms of overall 5- year survival rate is taken by combined treatment (surgery + radiotherapy) - 89.7%. The 2-nd place is taken by surgery or complex treatment (operations + palliative chemotherapy), 86.3% and 87.5% respectively. The 3-rd place is taken by combined treatment (surgery + radiotherapy + palliative chemotherapy) - 69.5%. While treating with radiotherapy in monoregimen overall 5-year survival rate amounted in 48.2%. Palliative chemotherapy takes the last place in the overall 5-year survival rate - 37.2%. Conclusion. This study allowed us to find the tasks that we need to solve in aim to improve the care service for patients with cervical cancer in the Zaporozhzhia region. Thus, it is necessary to establish a clear staging of cervical cancer, accurate, full and standardized data administration to the Local Cancer Registry about every case of the disease. Updating of local diagnostic and treatment guidelines for this disease is extremely important.